Laboratory investigation of freshwater production from a modified solar pond and comparison with a conventional solar pond - Mehdi Sedaghat; Farshad Farahbod (Solar Compass)
Water scarcity, particularly in recent years, has led to numerous challenges for humans worldwide. Decreasing precipitation coupled with a growing global population has exacerbated this problem. This study compares and evaluates the performance of a modified and a conventional solar pond for desalination and freshwater production. The modified pond is equipped with coiled pipes at its base, through which titanium dioxide nanofluid circulates. Originally, the improved pond used metal oxide nanoparticles due to their high conductive heat transfer coefficient. The research reveals that the temperature of the top layer of brine is, on average, 29 % higher than the ambient temperature. Additionally, the temperature of the second surface layer of brine is, on average, 18 % higher than the first, while the third surface layer is 11 % higher than the second. Similarly, the fourth surface layer is approximately 10 % warmer than the third, and the bottom layer is about 5 % warmer than the fourth. The study indicates that the maximum evaporation rate occurred in July, reaching 5.6 L/m²/day for the conventional solar pond and 21.1 L/m²/day for the modified pond. Based on this study, the maximum exergy was observed at 2 PM, with values of 2.5 % and 9.7 % for the conventional and modified solar ponds, respectively. The study shows that the maximum ambient temperature at 2 PM on June 17th was 38.9 °C, while on December 17th, it was 16.1 °C. Furthermore, the minimum ambient temperature occurred at 7 AM, with values of 26.4 °C and 7.8 °C for June 17th and December 17th, respectively.